(untitled) (Eurasian Journal of Ecology, 2018)
This assessment on the modification of biological objects in the environment when exposed to anthropogenic loads. Also made tests on the emissions of an industrial plant, the estimated waste types which are different from the products of the enterprise, their influence on atmospheric air, surface waters, soil. The impact on the environment solid, gaseous, wastewater, household and agricultural waste. Problems of health protection of the population of Kazakhstan is increasingly become a growing threat to national security. The analysis of the data characterizing the health status of the population and the human environment, suggests that is the case, the tense situation with the provision of sanitary-epidemiological wellbeing of the country. In the face of massive technogenic load increasingly difficult to contain the impact on humans of combined complex of habitat factors, which leads to stress and disruption of protective adaptation reserves of the body. One of the most powerful factors of influence on the environment and human health remain significant volumes of emissions of harmful substances, sewage, accumulation of toxic waste, the formation of large geochemical provinces of anthropogenic nature due to many years of use of the giants of industries in limited areas. Key words: biological objects, ecological crisis, environment, factors, human ecology, industrial waste, chemical pollutants